Target oxygen saturation range: 92–96% Versus 94–98%. Issue 1 (1st September 2016) - Beasley, Richard; Chien, Jimmy; Douglas, James; Eastlake, Leonie; Farah, Claude; King, Gregory; Moore, Rosemary; Pilcher, Janine; Richards, Michael; Smith, Sheree; Walters, Haydn
Abstract : This scientific letter considers the rationale for the target oxygen saturation measured by pulse oximetry (SpO2 ) range of 92–96% for oxygen therapy in adult patients without COPD or other conditions associated with chronic respiratory failure, recommended by the Thoracic Society of Australia and New Zealand, in contrast to the 94–98% target range recommended by the British Thoracic Society. We conclude from the available evidence that the SpO2 target of 92–96% may be preferable to 94–98%.